2013
DOI: 10.1371/journal.pone.0054507
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 Interactions with Chromatin and Identification of Its Novel Direct Target Genes in Lens and Forebrain

Abstract: Pax6 encodes a specific DNA-binding transcription factor that regulates the development of multiple organs, including the eye, brain and pancreas. Previous studies have shown that Pax6 regulates the entire process of ocular lens development. In the developing forebrain, Pax6 is expressed in ventricular zone precursor cells and in specific populations of neurons; absence of Pax6 results in disrupted cell proliferation and cell fate specification in telencephalon. In the pancreas, Pax6 is essential for the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 124 publications
3
72
0
Order By: Relevance
“…As a key transcription factor, PAX6 has been demonstrated to be involved in the development of the eye, central nervous system and pancreas (3,24). Previously, PAX6 was revealed to be involved in the regulation of malignant glioma (4,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key transcription factor, PAX6 has been demonstrated to be involved in the development of the eye, central nervous system and pancreas (3,24). Previously, PAX6 was revealed to be involved in the regulation of malignant glioma (4,25).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that PAX6 is crucial in the development of the central nervous system (3). Previously, several studies have suggested that PAX6 acts as a tumor suppressor in malignant glioma (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…While ZNRD1-AS has no known biological role, several lines of evidence suggest that one or both of HLA-A and ZNRD1 have neuronal functions (Boulanger, 2009;Elmer and McAllister, 2012;Xie et al, 2013) and possible roles in schizophrenia (Bergen et al, 2012; Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013b; McAllister, 2014) (in addition to the evidence for neuronal function of HLA class I proteins outlined in the Introduction). Both of these genes are expressed in the thalamus (Allen Brain Atlas: http://human.brain-map.org; Braineac: http://www.braineac.org/ (Ramasamy et al, 2014)), and Chip-seq data in mouse brain has suggested that their homologues (H2-K1 and Znrd1) are regulated by the transcriptional factor Pax6 (Xie et al, 2013), a major actor in the developing central nervous system. Notably Pax6 interacts with Baf150 and Baf177 to regulate cerebral size and thickness (Tuoc et al, 2013;Xie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these genes are expressed in the thalamus (Allen Brain Atlas: http://human.brain-map.org; Braineac: http://www.braineac.org/ (Ramasamy et al, 2014)), and Chip-seq data in mouse brain has suggested that their homologues (H2-K1 and Znrd1) are regulated by the transcriptional factor Pax6 (Xie et al, 2013), a major actor in the developing central nervous system. Notably Pax6 interacts with Baf150 and Baf177 to regulate cerebral size and thickness (Tuoc et al, 2013;Xie et al, 2013). Furthermore, both HLA-A and ZNRD1 contain SNPs associated with schizophrenia by GWAS; rs2524005 is intronic in HLA-A (Bergen et al, 2012) and rs8321 is in the 3 0 untranslated region of ZNRD1 (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Development 140 (5) with Pax6 ChIP data obtained with E15 WT cerebral cortex, lens and pancreas cells (Xie and Cvekl, 2011;Xie et al, 2013). Interestingly, Pax6 was bound to the promoters of ~20% of the genes regulated in either Pax6…”
Section: Research Articlementioning
confidence: 99%